EXCLUSION PASSIVATION STRATEGY OF REPRESENTATION OF SOCIAL ACTOR ON AUNG SAN SUU KYI CRITICISM IN THE CASE OF ROHINGYA CRISIS ON ONLINE MEDIA HEADLINES: A CDA APPROACH - Ali, Noval; Bustam, Muhammad Rayhan (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2020)
This research entitled â€œExclusion Passivation Strategy of Representation of Social Actor on Aung San Suu Kyi Criticism in The Case of Rohingya Crisis on Online Media Headlines (A CDA Approach)â€ Exclusion itself is a strategy to disappear the social actors from the text. This strategy is a part of Critical Discourse Analysis tool from Theo Van Leeuwen (2008:29). According to Theo van Leeuwen there are two kinds of exclusion, suppression and backrounding. Suppression is the exclusion that leaves no traces in the representation, excluding both the social actors and their activities, whereas backgrounding is the exclusion that leaves traces in the representation. However, in this article, the type of exclusion used is suppression, especially passivation strategy; the strategy is used as a limitation in the research for this article. There are 3 data collected when two data are pros with Suu Kyi criticism and one data sounded neutral with Suu Kyi criticism.